‘Dutchman, lazier than any other race of mankind’. Joseph Banks bezoekt de Nederlandse Republiek (1773) - Schilling, Renée (Studium, 2015)
‘Dutchman, Lazier than any other race of mankind’: Joseph Banks in the Dutch Republic.In 1773, the British scientist and explorer Joseph Banks (1743-1820) visited the Dutch Republic for a short holiday. By request of his sister Sarah, Banks kept a journal in which he wrote about his experiences in the Republic. These descriptions are remarkably negative about the Dutch, their culture and their scientific knowledge. It also gives a good insight in Banks’s personality. This article tries to answer the question why Banks is having such a bad time in the Dutch Republic. The article contains a short summary of the journal, an account of Banks’s earlier journey to Batavia with James Cook and a comparative analysis of other British travel accounts of the Dutch Republic in the eighteenth century.